Twisted tensor products of K 3 with K 3 - Arce, J.; Guccione, J.A.; Guccione, J.J.; Valqui, C. (Bellwether Publishing, 2021)
We describe all the twisted tensor products of K3 with K3, where K is an arbitrary field.
Keywords: Tensor (intrinsic definition); Mathematics; Pure mathematics; https://purl.org/pe-repo/ocde/ford#1.01.01